Proyecto de inversión para la introducción y comercialización de una bebida natural refrescante y multivitaminica hecha a base de carambola en la ciudad de Guayaquil - Sandoval Zúñiga, Verónica Carolina (2010)
Nowadays, there is tendency to take care, for that many people prefer the use of natural products that provide health benefits, is for this reason we seek the introduction of a multivitamin natural energy drink of carambola to satisfy this need. The market for this kind of fruit is not saturated wich is a great opportunity to become in one of the leading producers and marketers of natural energizing drink of carambola, considered an exotic fruit and a new product because it is a healthy way to refresh and nourish, this being a different way to enjoy this exquisite fruit rich in calcium and vitamins. As a result we obtained that the market would be willing to consume the product for the benefits and properties multivitamin provides health, to energize the body in a natural way without harming the body, also this product was found in distribution sites easier for our consumers purchase.